2018
DOI: 10.11113/jt.v80.11191
|View full text |Cite
|
Sign up to set email alerts
|

Elaeis Guineensis Leaves Extracts as Eco-Friendly Corrosion Inhibitor for Mild Steel in Hydrochloric Acid

Abstract: This manuscript presents a study on a green corrosion inhibitor extracted from Elaeis guineensis (EG) leaves for mild steel (MS) exposed to acidic condition. Weight loss measurement was conducted at various temperatures to investigate the corrosion inhibitive behaviour of the aqueous extract in 1 M HCl solution. Results demonstrated that both inhibition efficiency (η%) and surface coverage (θ) had increased with increasing inhibitor concentration, but decreased with increasing temperature. After immersion for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The charge transfer resistance, R t values are calculated from the difference in impedance at lower and higher frequencies, as suggested by several authors [26][27][28][29][30][31].…”
Section: Iii6 Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…The charge transfer resistance, R t values are calculated from the difference in impedance at lower and higher frequencies, as suggested by several authors [26][27][28][29][30][31].…”
Section: Iii6 Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…Previous investigations on mild steel in simulated 3.5 % NaCl Solution showed that the inhibition e ciency of Jatropha Curcas and Hibiscus Sabdariffa Calynx increases with increase in inhibitor concentrations 33 and disorders in the digestive, genito-urinary, respiratory, dermal, endocrine, and cardiovascular system 39 . Investigative studies revealed that oil palm leaves, and empty fruits bunch have corrosion inhibitory properties [40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have reported high inhibition e ciencies with inhibition e ciency increasing with increasing inhibitor concentration 40,[48][49][50][51][52][53] . Prior work indicates that the adsorption of plant extracts on mild and stainless-steel takes place by either physisorption and/or chemosorption depending on the plant extract phytochemicals and the corrosive media 31,42,54,55 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the renowned ways of controlling and reducing the corrosion rate of the low carbon steel is to apply organic inhibitors [15,[20][21][22][23][24][25][26][27]. These organic corrosion inhibitors are either simple or mixtures that are added to the aggressive environments in low quantities in order to reduce, control or even hinder reactions from occurring between the metal and its surroundings [28].…”
Section: Introductionmentioning
confidence: 99%